2005
DOI: 10.1051/0004-6361:20052707
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar extinction by spheroidal dust grains

Abstract: Abstract.Observations of interstellar extinction and polarization indicate that the interstellar medium consists of aligned nonspherical dust grains which show variation in the interstellar extinction curve for wavelengths ranging from NIR to UV. To model the extinction and polarization, one cannot use the conventional Mie theory which assumes the grains as solid spheres. We have used a T-matrix based method for computing the extinction efficiencies of spheroidal silicate and graphite grains of different shape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
2
27
2
Order By: Relevance
“…However, the required range of values for a max is probably unrealistic, given the observational constraints from the extinction curve. The interstellar extinction curve of regions of low extinctions is well reproduced by an MRN grain size distribution of spheroidal grains with a max ¼ 0:25 m (Gupta et al 2005). If this is the value of a max in regions of relatively low density, Figure 6 shows that E(H À K ) can increase with density only by less than a factor of 2 as the maximum grain size grows from a max ¼ 0:25 to 0.6 m. In other words, neglecting the process of grain growth can cause errors only of less than a factor of 2 in the dust column density based on E(H À K ), which is insufficient to explain the difference between the gas and the dust power spectra.…”
Section: Grain Growth and Nir Extinction Efficiencymentioning
confidence: 83%
See 1 more Smart Citation
“…However, the required range of values for a max is probably unrealistic, given the observational constraints from the extinction curve. The interstellar extinction curve of regions of low extinctions is well reproduced by an MRN grain size distribution of spheroidal grains with a max ¼ 0:25 m (Gupta et al 2005). If this is the value of a max in regions of relatively low density, Figure 6 shows that E(H À K ) can increase with density only by less than a factor of 2 as the maximum grain size grows from a max ¼ 0:25 to 0.6 m. In other words, neglecting the process of grain growth can cause errors only of less than a factor of 2 in the dust column density based on E(H À K ), which is insufficient to explain the difference between the gas and the dust power spectra.…”
Section: Grain Growth and Nir Extinction Efficiencymentioning
confidence: 83%
“…We cannot entirely rule out this explanation, given the still limited knowledge of dust grain properties (different grain models can satisfy the same observational constraints, and most grain models are not realistic enough, as they overestimate the abundance of carbon and silicon relative to interstellar medium values in order to explain the extinction curve; Gupta et al 2005). However, based on available models, the UV extinction curve is best fit by a value of a max ¼ 0:25 m in regions of relatively low extinction.…”
Section: Discussionmentioning
confidence: 99%
“…This figure also shows the inclusions embedded in the host oblate spheroid. Oblate spheroids were selected based on the numerous results of previous studies (Greenberg & Hong 1975;Henning & Stognienko 1993;O'Donnell 1994;Gupta et al 2005) that showed that oblate spheroids represent properties of circumstellar dust particles better; specifically, this model provides a good fit to the observed polarization across the 10 μm feature (Lee & Draine 1985).…”
Section: Composite Grains and Ddamentioning
confidence: 99%
“…The influence of the type of spheroidal grain on the polarisation is discussed by Voshchinnikov (2004). Dust models considering spheroidal particles that fit the average Galactic extinction and polarisation curves were presented by Gupta et al (2005); Draine & Allaf-Akbari (2006); and Draine & Fraisse (2009). The observed interstellar extinction and polarisation curves towards particular sight lines have been modelled by Voshchinnikov & Das (2008) and Das et al (2010).…”
Section: Introductionmentioning
confidence: 99%